The contribution of mitochondrial function to the energetics of cell cycle progression - Sweet, Susan (My University, 2000)
Mitochondria play a critical role in the provision of energy to individual cells through the synthesis of ATP. The relationship between mitochondrial energy production and cell cycle progression has been explored in this work with the intention of defining the fuel requirements of the cell cycle engine. Because mitochondrial physiology and cell division proved to be intimately linked, we also examined the feasibility of disrupting mitochondrial properties in order to alter cell cycle dynamics. We show that the rate of utilization of mitochondrially-derived ATP fluctuates throughout the cell cycle and that stages where ATP levels are lowest correspond to stages most sensitive to pharmacologic inhibition of mitochondrial function. These particular transition points comprise theoretical "energetic checkpoints" of cell cycle progression. It is here that the biochemical events that are sensitive to changes in the cellular energy status will determine whether the cell continues through its cycle or pauses until a favourable energetic balance is restored. The increase in the number of cells in the G1 component of the cell cycle that results from antagonizing mitochondrial function is accompanied by an augmented proportion of persistently active Retinoblastoma protein (Rbp). Failure to inactivate this tumour suppressor protein, whose role it is to brake cell cycle progression in response to suboptimal conditions, does not result from an upregulation of the "classical" G1 inhibitory proteins but rather does so secondary to a decrease in the availability of a critical G1 cyclin. This sensitive regulatory protein, cyclin D, is essential for the activation of kinases responsible for the initial phosphorylation of Rbp, which renders it inactive and allows passage out of the G1 component of the cell cycle. This is the first work to report cell cycle-specific periods of increased ATP utilization which correlate with checkpoints through which a cell will not pass if its energetic balance is sufficiently disrupted. We also demonstrate that changes in mitochondrial function elicit changes in the core proteins of the cell cycle machinery suggesting some intracellular link between the energy balance within the cell and the proteins responsible for cell cycle progression. Finally this report confirms previous suggestions that mitochondria represent viable targets for altering the division characteristics of a cell population, particularly in the context of the altered mitochondrial phenotype of many tumour cells.
Keywords: Medical Sciences; Medical Sciences